Development of Mangrove Ecosystem E-encyclopedia as a Reference Source to Improve Information Literacy Skills and Environmental Care Attitudes of Students - Ratminingsih, Ratminingsih; Subiantoro, Agung Wijaya (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2023)
This study aims to produce a development product that is feasible and effective to use for science learning in schools. The product developed is an e-encyclopedia of mangrove ecosystems. This study uses the Research and Development (R&D) model developed by Borg & Gall. The subjects of the limited trial consisted of 15 students of class VII. In comparison, the field trial consisted of 52 students from VII-G and VII-E of SMP IT Abu Bakar Yogyakarta. The data collection instruments included interviews, field observations, information literacy evaluation questions, and student environmental care attitude questionnaires. The field trial design used a pretest-posttest control group design. The results showed that: (1) the developed mangrove ecosystem e-encyclopedia is very suitable for use in science learning; (2) the e-encyclopedia of mangrove ecosystems is effective for improving students' information literacy skills and environmental care attitudes. Development of Mangrove Ecosystem E-encyclopedia as a Reference Source to Improve Information Literacy Skills and Environmental Care Attitudes of Students.